Making peer-feedback more efficient: what conditions of its delivery make the difference?. Issue 2 (23rd February 2022) - Armengol-Asparó, Carme; Mercader, Cristina; Ion, Georgeta
ABSTRACT: Peer feedback benefits students' learning at the university level. However, how it makes an impact on students' learning and which defining factors in its design wield more significant influence are aspects that continue to require further analysis. This study is dedicated precisely to analyse how different feedback conditions impact students' perception of their learning. Through a questionnaire administered to a sample of 410 university students, we inquire about how the different conditions under which the feedback is designed – such as privacy (anonymous or not), contact (personal or virtual), delivery channel (oral, written or mixed) and consensus (individual or in a group) – impact the improvement of learning tasks and the development of the students' inter- and intrapersonal skills. The results reveal that students perceive that they learn more when they give feedback than when they receive it, and that there are certain conditions that are better suited to others for absorbing what has been learnt. The study reveals that in order to maximise its effects, the instructional design of peer feedback must offer spaces to carry it out face-to-face – anonymously – with a mixed channel of delivery (complementing written comments with oral feedback) and that the feedback be agreed upon in a group, both when it is given and when it is received.